Fiqh Peradaban and the Actualization of Religious and State Life in the Modern Society - Latif, Mukhlis; Mutawalli, Muhammad; Paidi, Zulhilmi (FIKRAH, 2023)
This paper discusses fiqh peradaban (Islamic jurisprudence for civilization) as a concept that emphasizes the importance of resolving conflicts and prioritizes fundamental ethics as an aspect of morality in order to create peace in living religious and state life. More specifically, it highlights the importance of fiqh peradaban in maintaining social cohesion and national unity in a bhinneka-nuanced society. In this sense, fiqh peradaban functions as a framework for building unity and harmony amidst diversity. This research is library research; it reviews library resources related to the concept of fiqh peradaban. This research uses a qualitative approach and presents data descriptively. The data collected in this research includes the intersection between the UN Charter and Islamic law; the relationship between Islam, the state, and democracy; the role of Islam in modern society and state; and the concept of fiqh peradaban as a balanced control between the state and religion. In general, the results of this study show that fiqh peradaban has a crucial role in overcoming conflicts and problems that arise in religious and state life. These conflicts and problems must be resolved by the state because they can threaten religious harmony and national unity. However, the state's involvement in religious and spiritual affairs may create its own problems. It is here that fiqh peradaban is present as a solution because it offers foundational ethics for modern society.